VULNERABILITY INDEX ASSESSMENT OF THE EROSIVE ATHEROSCLEROTIC PLAQUE ON ENDARTERECTOMY SPECIMENS - Doina Butcovan; Cezarina Dumitrescu; Elena Stefanachi; Catalina Arsenescu-Georgescu (Romanian Society of Oral Rehabilitation, 2014)
Background Atherosclerosis is an arterial inflammatory process which causes associated tissue ischemia of different degrees. It is not yet calculated an index of plaque vulnerability as a histological marker of acute cardiac event risk at these patients. Aim of the study This retrospective study aimed to answer the question of whether the index of plaque vulnerability can appreciate the risk of atherothrombosis of the erosive plaques using histological measurements. Material and methods 30 patients were included in the study. American Heart Association (AHA) classification was used for appreciating the histological degree of ATS lesions on endarterectomy pieces. In all patients, intima-media thickness (IMT), erosion depth, and parietal thrombosis area were assessed. Results The proposed vulnerability index showed that about 50% of patients have a medium risk of plaque vulnerability and of associated acute coronary syndrome (ACS). Conclusions The index of plaque vulnerability may be used as a reference in ATS assessment by using intravascular ultrasound (IVUS) methods.